Malaysian Civil Service : Problems And Challenges - Yaakob, Ahmad Faiz; Salleh, Asri; Jusoff, Kamaruzaman; Hussain, Mohammad Khairul Anwar (Universiti Teknologi MARA (Terengganu), 2012)
The Malaysian civil service for so long has maintained the tradition of being politically neutral. However, maintaining impartiality throughout is relatively difficult especially when a ruling political party has been at the helm of political power for a very long time. In other words, it is not easy to break the close relationship the Malaysian politicians and the government’s senior officers have built as a result of the ruling political party’s uninterrupted years in power since the country’s independence in 1957. The objective of this paper is to analyze the capacity and the professionalism of the Malaysian civil service, particularly the Malaysian senior civil servants. The paper argues, among factors that have the inherent possibility and aptitude to compromise the capacity and professionalism of the top management are; (i) political executive dominance, (ii) ‘ethnicized civil service’ and (iii) new mechanism of public governance.